Prison cell spatial density and infectious and communicable diseases: a systematic review - Simpson, Paul L (BMJ Open, 2019)
OBJECTIVE: To summarise the extent and quality of evidence on the association between prison cell spatial density (a measure of crowding) and infectious and communicable diseases transmission among prisoners. DESIGN: Systematic review. DATA SOURCES: Embase, PubMed, Medline, Scopus, Web of Science, PsycINFO, PsycExtra, ProQuest Databases, ProQuest Dissertations and Theses Global, Index to Legal Periodicals, InformitOnline, Cochrane Library, Criminal Justice Abstracts and ICONDA were searched to 31 December 2018. ELIGIBILITY CRITERIA: Studies that reported on the association between prison cell spatial density (measured in square feet or square metres of cell floor area per person) and infectious and communicable diseases in juvenile and adult populations incarcerated in a correctional facility. DATA EXTRACTION AND SYNTHESIS: A review protocol was developed in consultation with an advisory panel. Two reviewers independently extracted data and used the Australian National Health and Medical Research Council’s (NHMRC) checklist to critically appraise individual studies. An assessment of the overall body of the evidence was conducted using the NHMRC’s Evidence Scale and Statement Form. RESULTS: A total of 5126 articles were initially identified with seven included in the review from Pakistan (2003), Chile (2016), Nigeria (2012, 2013) and the USA (1980s). Infectious and communicable disease outcomes included pneumococcal disease/acute pneumonia, Mycobacterium tuberculosis, latent tuberculosis infection, infectious skin conditions and contagious disease reporting to the prison clinic. Five articles reported statistically significant positive associations but were countered by associations possibly being explained by chance, bias or confounding factors. Heterogeneity prevented meta-analysis. CONCLUSION: Overall, the body of evidence provides some support for an association between prison cell special density and infectious and communicable diseases, but care should be taken in the interpretation and transferability of the findings. Future research and policy responses should adequately consider prospective mediating factors implicated in associations between cell spatial density and health effects.